Clinical significance of bile reflux into the pancreatic duct without pancreaticobiliary maljunction assessed by intraoperative cholangiography. Issue 3 (10th March 2015) - Ueno, Kimihiko; Ajiki, Tetsuo; Murakami, Sae; Fujita, Tsunenori; Matsumoto, Taku; Shinozaki, Kenta; Fukumoto, Takumi; Ku, Yonson
Abstract Introduction Bile reflux into the pancreatic duct (BRPD) is sometimes demonstrated during intraoperative cholangiography (IOC) even in patients without pancreaticobiliary maljunction. However, the clinical significance of this finding in laparoscopic and open cholecystectomy is unclear. Methods Among 484 patients who underwent cholecystectomy (372 laparoscopic, 112 open), patients whose pancreatic duct was depicted in IOC were selected. The value of pancreatic amylase (p‐amylase) of the gallbladder bile, histological changes, and the immunohistochemical expression of proliferating cell nuclear antigen (PCNA) in the gallbladder mucosa were analyzed in patients with BRPD. The data were then compared to those in patients without BRPD whose gallbladder bile p‐amylase was measured (control group, n = 20). Results The success rate of IOC was 93.6%. The rate of BRPD in laparoscopic and open cholecystectomy was 5.2% and 5.7%, respectively. The value of gallbladder bile p‐amylase in patients with BRPD was significantly higher than in the control group (790.5 vs 14.0 IU/L, P = 0.034). The value of the PCNA labeling index in patients with BRPD was significantly higher than that of the control group (15.4% vs 4.1%, P = 0.0026). Among the 24 patients with BRPD, pathological changes in the gallbladder mucosa were detected in five (two hyperplasia, three metaplasia), but there was no correlation between the presence of pathological change and PCNA labeling index or gallbladder bile p‐amylase. Conclusions IOC could detect BRPD both in laparoscopic and open cholecystectomy at a similar rate. Patients with BRPD had high levels of gallbladder bile p‐amylase and PCNA labeling index, findings similar to those in patients with pancreaticobiliary maljunction.